Analisis Yuridis atas Tindak Pidana Distribusi Pangan Tanpa Izin Edar di Pekanbaru - Panah Grosman, Kingkel (Journal of Society and Development, 2023)
This research aims to analyze the juridical aspects of business operators who commit the crime of distributing food without a distribution permit in Pekanbaru, as reflected in Decision No. 960/Pid.Sus/2014/PN.Pbr. The study employs a normative legal research method with a descriptive-analytical approach. The data used are secondary, including primary legal materials, secondary legal materials, and tertiary legal materials. Data analysis was conducted qualitatively by comparing the data with relevant legal regulations and expert opinions. The research reveals that the application of criminal law against business operators who distribute food without a permit is based on the fulfillment of legal elements as stipulated in Article 58(k) of Law No. 7 of 1996 on Food. The court sentenced the defendant, Ati, to four months in prison, suspended for one year, and ordered the destruction of the seized products. The findings also indicate a need for more rigorous enforcement and awareness-raising about the importance of food safety regulations among business operators. This study contributes to the understanding of the legal responsibilities of business operators in ensuring food safety and the role of the judiciary in enforcing these regulations. It highlights the importance of adherence to food safety laws to protect consumers and prevent legal repercussions for businesses. The research provides a comprehensive analysis of the legal framework surrounding food distribution without a permit in Indonesia, offering insights into the challenges of enforcing food safety laws at the local level.